Description of formal thinking ability - Bali Yana Fitri (Universitas Negeri Padang, 2023)
The Formal thinking ability is the ability to think in the face of hypothetical situations abstractly and can reason logically. When students reach formal thinking skills, they will have no difficulty understanding the concept of hydrolysis which is abstract. Based on the daily test scores for class XI IPA SMAN 4 Padang, it is known that 30% of students have not achieved completeness in hydrolysis. The incompleteness of some students indicates that there are still students who have not reached the level of formal thinking skills. Therefore, it is necessary to describe the level of students' formal thinking skills. This research was conducted to describe: the level of students' formal thinking skills, the type of research is descriptive. The research sample was students of class XI IPA AT SMAN 4 padang, who were obtained using cluster random sampling. The research instrument was a formal thinking ability test (buney test). In the formal thinking test, trials were carried out to see the value of item validity and reliability. The results of the study showed that:63.79% of class xi ipa sman 4 padang students had reached the level of formal thinking skills.